2014
DOI: 10.1371/journal.pone.0086775
|View full text |Cite
|
Sign up to set email alerts
|

Velocity and Directionality of the Electrohysterographic Signal Propagation

Abstract: ObjectiveThe initiation of treatment for women with threatening preterm labor requires effective distinction between true and false labor. The electrohysterogram (EHG) has shown great promise in estimating and classifying uterine activity. However, key issues remain unresolved and no clinically usable method has yet been presented using EHG. Recent studies have focused on the propagation velocity of the EHG signals as a potential discriminator between true and false labor. These studies have estimated the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 36 publications
3
34
2
Order By: Relevance
“…Studies on the propagation of the uterine electrical busts on women in labour reveal, similar to the propagation of the pressure wave (Caldeyro-Barcia & Alvarez 1952), a predominantly downward propagation and a preferred origin of the burst in the upper/ovarian region of the uterus in women as well as in the guinea-pig (Planes et al 1984, Norwitz et al 1999, Lammers et al 2008, Mikkelsen et al 2013. However, in women, upward and multidirectional propagation patterns, including simultaneous upward and downward propagation, have also been frequently reported while analysing the myometrial electrical burst , Mikkelsen et al 2013, Lange et al 2014. Analysis of the centre of uterine activity, obtained by a Gaussian fitting of the spatial distribution of the burst energy along a two-dimensional grid of electrodes, revealed that women who delivered successfully vaginally, in contrast to those who had arrested labour, had a predominant upward direction of the uterine activity centre (Buhimschi 2009, Euliano et al 2009).…”
Section: Pattern Of Propagationmentioning
confidence: 83%
See 2 more Smart Citations
“…Studies on the propagation of the uterine electrical busts on women in labour reveal, similar to the propagation of the pressure wave (Caldeyro-Barcia & Alvarez 1952), a predominantly downward propagation and a preferred origin of the burst in the upper/ovarian region of the uterus in women as well as in the guinea-pig (Planes et al 1984, Norwitz et al 1999, Lammers et al 2008, Mikkelsen et al 2013. However, in women, upward and multidirectional propagation patterns, including simultaneous upward and downward propagation, have also been frequently reported while analysing the myometrial electrical burst , Mikkelsen et al 2013, Lange et al 2014. Analysis of the centre of uterine activity, obtained by a Gaussian fitting of the spatial distribution of the burst energy along a two-dimensional grid of electrodes, revealed that women who delivered successfully vaginally, in contrast to those who had arrested labour, had a predominant upward direction of the uterine activity centre (Buhimschi 2009, Euliano et al 2009).…”
Section: Pattern Of Propagationmentioning
confidence: 83%
“…, Lange et al . ). Analysis of the centre of uterine activity, obtained by a Gaussian fitting of the spatial distribution of the burst energy along a two‐dimensional grid of electrodes, revealed that women who delivered successfully vaginally, in contrast to those who had arrested labour, had a predominant upward direction of the uterine activity centre (Buhimschi , Euliano et al .…”
Section: Pattern Of Propagationmentioning
confidence: 97%
See 1 more Smart Citation
“…However, only one dimension of propagation is considered at a time, which is based on the estimation of time delays between spikes. In comparison, Lange et al (Lange et al, 2014) estimate the PV of the entire EHG burst that occurs during a contraction. This has been achieved by calculating the bursts corresponding to a full contraction event.…”
Section: Related Studiesmentioning
confidence: 99%
“…However, only one dimension of propagation is considered at a time, which is based on the estimation of time delays between spikes. In comparison, Lange et al (Lange et al, 2014) estimate the PV of the entire EHG bursts that occur during a contraction by calculating the bursts corresponding to a full contraction event. The results illustrate that the estimated average propagation velocity is 2.18 (60.68) cm/s.…”
Section: Related Studiesmentioning
confidence: 99%